DIGITAL MARKETING AND MARKET ENTRY AGILITY ON THE MARKETING PERFORMANCE OF PONTIANAK CULINARY MSMES - Ariadi, Ariadi; Muis, Mahlia; Cokki, Cokki (International Journal of Application on Economics and Business, 2024)
This study examines the influence of digital marketing activities and market entry agility on marketing performance of Pontianak Culinary MSMEs. The sample size for this study consists of 31 culinary entrepreneurs in Pontianak. The method used in this study to collect the data is convenience sampling where questionnaires were distributed directly to the respondents. The results of this study show that marketing performance is affected directly by market entry agility, but not by digital marketing, while market entry agility is directly affected by digital marketing. There is also an indirect effect of digital marketing on marketing performance through market entry agility. Additionally, this study suggests that Pontianak culinary MSMEs should enhance their digital marketing and market entry agility to improve marketing performance.